The Moor’s Political Colour: Race and Othello in Poland - Kowalcze-Pawlik, Anna (Multicultural Shakespeare: Translation, Appropriation and Performance, 2020)
This paper provides a brief outline of the reception history of Othello in Poland, focusing on the way the character of the Moor of Venice is constructed on the page, in the first-published nineteenth-century translation by Józef Paszkowski, and on the stage, in two twentieth-century theatrical adaptations that provide contrasting images of Othello: 1981/1984 televised Othello, dir. Andrzej Chrzanowski and the 2011 production of African Tales Based on Shakespeare, in which Othello’s part is played by Adam Ferency (dir. Krzysztof Warlikowski). The paper details the political and social contexts of each of these stage adaptations, as both of them employ brownface and blackface to visualise Othello’s “political colour.” The function of blackface and brownface is radically different in these two productions: in the 1981/1984 Othello brownface works to underline Othello’s overall sense of alienation, while strengthening the existing stereotypes surrounding black as a skin colour, while the 2011 staging makes the use of blackface as an artificial trick of the actor’s trade, potentially unmasking the constructedness of racial prejudices, while confronting the audience with their own pernicious racial stereotypes.